2021
DOI: 10.3390/jcm10061325
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Colon Tissue of Pediatric Ulcerative Pancolitis Patients Allow Detection and Prognostic Stratification

Abstract: Prevalence of inflammatory bowel disease has been on the rise in recent years, especially in pediatric populations. This study aimed to provide precise identification and stratification of pediatric patients with diagnosed ulcerative colitis (UC) according to the severity of their condition and the prediction for standard treatment according to the specific expression of candidate miRNAs. We enrolled consecutive, therapeutically naïve, pediatric UC patients with confirmed pancolitis. We examined formalin-fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…At present, miRNA biomarkers in UC are mainly studied for clinical diagnosis and monitoring, however, miRNA biomarkers seem to have other values. Due to the broad regulatory effects of miRNA, it is associated with almost all clinical reactions, such as in predicting disease recurrence (Jabandziev et al, 2021), therapeutic escalation (Kalla et al, 2020), and response to drug therapy (Batra et al, 2020). Although this aspect is currently under-researched, they do represent a valuable direction of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, miRNA biomarkers in UC are mainly studied for clinical diagnosis and monitoring, however, miRNA biomarkers seem to have other values. Due to the broad regulatory effects of miRNA, it is associated with almost all clinical reactions, such as in predicting disease recurrence (Jabandziev et al, 2021), therapeutic escalation (Kalla et al, 2020), and response to drug therapy (Batra et al, 2020). Although this aspect is currently under-researched, they do represent a valuable direction of research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Morilla et al used a panel of miRNA biomarkers (has-miR-3934, hsa-miR-100, hsa-miR-718, hsa-miR-193b, hsa-miR-3150a-5p, hsa-miR-1260b, hsa-miR-938, has-miR-518b, andhsa-miR-1468) to distinguish steroidresistant acute severe ulcerative colitis (ASUC) patients with high accuracy (AUC 0.87) (Morilla et al, 2019). Jabandziev et al analyzed miRNA expression in colonic tissue of 60 pediatric UC patients and found four panels of miRNAs, which were used to distinguish pediatric UC patients from healthy controls AUC 0.99), to detect severity in pediatric UC patients ACU 0.73), to detect disease relapse within one year of treatment AUC 0.73) and to diagnose UC patients with primary sclerosing cholangitis (miR-142-3p, miR-146a-5p, miR-223-3p, let-7i-5p, miR-192-5p and miR-194-5p, AUC 0.858) (Jabandziev et al, 2021).…”
Section: Mirnas Are Specifically Expressed In Ulcerative Colitis Mirnas As Biomarkers For Diagnosis Monitoring and Prognosis Of Ulcerativmentioning
confidence: 99%
“…miR-375 was predicted and proved to be a target miRNA of SNHG5. miR-375 was evidenced to be down-regulated in UC [ 28 , 29 ]. It is down-regulation activated inflammatory signaling in UC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated miR-375 contributes to the progression of oral squamous cell carcinoma [ 24 ], prostate cancer [ 25 ], CRC [ 26 ], and osteosarcoma [ 27 ]. Furthermore, miR-375 was down-regulated in UC [ 28 , 29 ]. In this study, the potential roles of SNHG5 and miR-375 in UC were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of targeted therapy, more attention has been turned to predictive biomarkers [ 6 ]. However, there is currently no biomarker reaching a sufficient specificity and sensitivity enabling the precise personalization of the therapy [ 5 ], although great scientific effort has been focused on searching for biomarkers in many human diseases [ 7 ], including RCC [ 5 ]. Among the potential molecules feasible as biomarkers, long non-coding RNAs have been studied excessively.…”
Section: Introductionmentioning
confidence: 99%